Passenger air transportation market in Europe - I. P. Stecenko; A. V. Parkhimovich (Научный вестник МГТУ ГА, 2020)
The civil aviation is a systemically important sector of the European economy. In 2015, a new development strategy defining the role of air transport in passenger communications was adopted. The implementation of the strategy provides for, among other things, tickets cost reduction, which will have its impact on the population mobility. In this context, the article considers the priorities of the development strategy, noting that the demand for passenger air travel depends on multiple factors. They can be aggregated into four groups: social stability, macroeconomic, intrasectoral, and inter-transport factors. Their influence on the demand value varies by its degree, while being both price-based and non-price-based in nature. The article defines the leaders of the passenger air transportation market, addresses the problems obstructing the air transportation network development. It also highlights the European passenger air transportation market specifics and the prospects for development of a unified transport system to ensure a positive socio-economic effect in the development of the economy. A high level of competition with a comparable level of service quality calls for new forms of relationship with consumers. With a convenient passenger transportation infrastructure built nowadays in Europe, there are companies operating on the market that offer fairly expensive as well as low-cost transportation service. In addition, the level of average per capita income in Europe is quite high. All combined, these factors predetermine increased demand for transportation by air. Given these conditions, adoption of innovations and digital technologies, together with the encouragement of investments, should present a stimulus for growth. The adoption of the said measures will lead to passenger service quality improvement, traffic turnover and airlines’ revenues increase, and more job opportunities. Reliability, safety, environment are regarded as strategic priorities.